Power generation and thermoelectric cooling enabled by momentum and energy multiband alignments - Qin, Bingchao; Wang, Dongyang; Liu, Xixi; Qin, Yongxin; Dong, Jin-Feng; Luo, Jiangfan; Li, Jing-Wei; Liu, Wei; Tan, Gangjian; Tang, Xinfeng; Li, Jing-Feng; He, Jiaqing; et al. (Science (American Association for the Advancement of Science), 2021)
Thermoelectric materials can convert heat into electricity or be used as the basis of cooling devices. Qin et al . found that doping a tin selenide thermoelectric material with lead and sodium improved the room temperature thermoelectric properties, an effect created by manipulation of the electronic bands. The authors showed that the material could be used not only for power generation but also cooling. If optimal contact materials are identified, then this approach may be attractive for future applications. —BG Wide-bandgap SnSe crystals can be used for both power generation and thermoelectric cooling. Thermoelectric materials transfer heat and electrical energy, hence they are useful for power generation or cooling applications. Many of these materials have narrow bandgaps, especially for cooling applications. We developed SnSe crystals with a wide bandgap ( E g ≈ 33 k B T ) with attractive thermoelectric properties through Pb alloying. The momentum and energy multiband alignments promoted by Pb alloying resulted in an ultrahigh power factor of ~75 μW cm –1 K –2 at 300 K, and an average figure of merit ZT of ~1.90. We found that a 31-pair thermoelectric device can produce a power generation efficiency of ~4.4% and a cooling Δ T max of ~45.7 K. These results demonstrate that wide-bandgap compounds can be used for thermoelectric cooling applications.